AKIBAT HUKUM PELAKSANAAN PERSIDANGAN E-COURT STUDI PUTUSAN 17/G/2021/PTUN.TPI TERHADAP MODERNISASI PERADILAN - Lumban Tobing, Remy Fillippine Astrada; Ukas, Ukas (LPPM Universitas Putera Batam, 2024)
ABSTRACTThe development of the trial was renewed through perma number 1 of 2019 concerning the administration ofcases and trials in courts electronically. Through the e-court, the judicial process is carried out electronically.However, the verification process is still carried out according to the usual procedure. The conclusion of thewriting is an analysis of the trial process number 17/g/2021/ptun.tpi on the evidentiary agenda related toemployment disputes